In Vitro Propagation of an Endangered Helianthus verticillatus by Axillary Bud Proliferation - Nowakowska, Marzena (Plants (Basel), 2020)
Helianthus verticillatus (Asteraceae), whorled sunflower, is a perennial species restricted to a few locations in the Southeastern United States. Habitat loss has caused H. verticillatus to become rare, and since 2014, it has been federally listed as an endangered species. As a part of the recovery plan for the restoration and protection of H. verticillatus, an efficient micropropagation protocol based on axillary shoot proliferation was developed. Various concentrations of 6-benzylaminopurine (BAP; 0 to 4.44 µM) were examined for their morphogenetic potential in the regeneration of six genotypes of H. verticillatus from the nodal explants derived from greenhouse-grown plants. Both the BAP concentration and genotype had significant effects on the regeneration capacity of H. verticillatus. Although the induced buds were observed on ½-strength Murashige and Skoog medium without plant growth regulators, a higher rate of induction and bud development were achieved on media with either 0.88 or 2.22 µM BAP, regardless of the genotype. Successful rooting of the induced shoots was achieved within four weeks after the transfer from the induction medium to the fresh ½-strength MS medium, but the rooting efficiency was dependent on the plant’s genetic background. Regenerated plantlets, with well-developed shoots and roots, were acclimatized successfully to greenhouse conditions with a 97% survival rate. Simple sequence repeats (SSRs) markers were employed to assess the genetic uniformity of the micropropagated plants of H. verticillatus. No extraneous bands were detected between regenerants and their respective donor plants, confirming the genetic fidelity and stability of regenerated plants. To our knowledge, the protocol developed in this study is the first such report for this endangered species.